Smart Antenna RF Front-end for WLAN and SDARS - Bai, Yu (University of Waterloo, 2006)
This thesis presents RF front-end system design for both WLAN (Wireless Local Area Network) and SDARS (Satellite Digital Audio Radio System) applications using adaptive smart antenna technique. It is important to understand that smart antenna system with adaptive beam-forming provides the following advantages: 1. It can concentrate radio transmission on specific directions by modifying transmit/receive phase and amplitude characteristics, and therefore provides greater coverage and increased capacity. 2. It can greatly reduce multi-path fading effect and co-channel interference. This thesis first presents a complete 4-element smart antenna system for IEEE 802.11b/g WLAN applications. The prototype presented can interconnect with an of-the-shelf WLAN network card. The system is controlled via a microcontroller that adjusts the array pattern to capture the best signal. Measurements show that the system can increase the RSSI (Received Signal Strength Indicator) level significantly and therefore the SNR (Signal to Noise Ratio). This prototype is the first step towards a novel DBF (Digital Beam-Forming) smart antenna architecture. The second part of the thesis presents a 2-element smart antenna system for SDARS application. This prototype can be connected with an of-the-shelf SDARS digital receiver. The system was tested in a chamber and measurements show a controlled beam and increased gain. Ansoft HFSS was used to simulate the 2-element smart antenna and validate the testing results.
Keywords: Electrical and Computer Engineering